FATIGUE PERFORMANCE OF ASPHALT CONCRETE CONTAINING A GEOCOMPOSIT - Fauzi, Ahmad
FATIGUE PERFORMANCE OF ASPHALT CONCRETE CONTAINING A GEOCG1POSITE, Ahmad Fauzi, 2000, Program Magister Sistem dan Teknik Jalan Raya, Institut Teknologi Bandung The asphalt layer in a pavement must have adequate stiffness, flexibility, durability, stability and impermeability. Continuously graded asphalt concrete has good resistance to permanent deformation, but is less resistant to fatigue cracking. The capability of the asphalt layer to withstand fatigue cracking may be improved by using a geocomposite such as Tensar AR-G. The purpose of the investigation described in this thesis was to evaluate the laboratory fatigue performance of preconditioned and non-conditioned asphalt concrete without a geocomposite and also preconditioned asphalt concrete with and without a geocomposite. The laboratory tests were conducted in the controlled-stress mode in the DARTEC fatigue machine and parameters investigated included the fatigue life, the initial stiffness and the cracking mechanism. The results indicate that the inclusion of a geocomposite sheet one centimetre from the bottom of the preconditioned asphalt concrete beam increases the fatigue life at a given stress level by a factor ranging from 24.86 to 39.50. Analysis of the cracking mechanism showed that crack propagation was retarded by a geocomposite and the rate of crack propagation was reduced. The number of crack propagation cycles for preconditioned asphalt concrete with geocomposite ranges from 35,493 to 899,008 and from 417 to 3,772 for preconditioned asphalt concrete without geocomposite; and also the number of crack propagation cycles for non-conditioned asphalt concrete without geocomposite ranges from 122 to 1,159. However, inclusion of a geocomposite does not influence the initial stiffness or initial strain. The initial stiffness ratio between the preconditioned asphalt concrete with and without geocomposite was 1.07. Analysis of the fatigue characteristics of preconditioned and non-conditioned asphalt concrete without geocomposite indicates that the preconditioning process (aging of the mixture in an oven at 135Â°C for 4 hours prior to compaction) increased the fatigue life by a factor ranging from 2.3 to 3.2 depending on stress level; the initial stiffness increase by a factor of 1.6. When analysed on the basis of initial strain, fatigue lives of preconditioned and non-conditioned samples are virtually identical at the same strain level